2016
DOI: 10.1007/s12671-016-0596-7
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness In Parenting Questionnaire (MIPQ): Development and Validation of a Measure of Mindful Parenting

Abstract: First, I need to thank my dissertation chair, Dr. David Reitman, for his commitment and support during this challenging research endeavor. Thank you for your time, insight, and belief in me as I worked through this multiphase project. I would also like to thank my committee members, Dr. Ryan Black and Dr. Barry Nierenberg, for their guidance. Dr. Black, your enthusiasm for measure development is contagious, and I sincerely appreciate all the time you spent with me trying out new programs and running syntax. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(108 citation statements)
references
References 85 publications
(265 reference statements)
5
72
0
16
Order By: Relevance
“…According to these data, the majority of respondents are mothers and generally both mothers and fathers is in state of mindful parenting. Furthermore, the domination of 'high' category of mindful parenting indicating that parents in Bandung are able to demonstrate attitude of being in the moment with their children as well as possess high selfefficacy as one of components in mindful parenting based on previous studies found in [8]. These results also suggest that since woman are biologically and evolutionarily better prepared than men in the role of child rearing, they tend to be more willing to adopt and implement warmth, compassion, and mindful attitudes towards their children [9].…”
Section: Mindful Parentingmentioning
confidence: 95%
See 1 more Smart Citation
“…According to these data, the majority of respondents are mothers and generally both mothers and fathers is in state of mindful parenting. Furthermore, the domination of 'high' category of mindful parenting indicating that parents in Bandung are able to demonstrate attitude of being in the moment with their children as well as possess high selfefficacy as one of components in mindful parenting based on previous studies found in [8]. These results also suggest that since woman are biologically and evolutionarily better prepared than men in the role of child rearing, they tend to be more willing to adopt and implement warmth, compassion, and mindful attitudes towards their children [9].…”
Section: Mindful Parentingmentioning
confidence: 95%
“…The results are expected to illustrate whether parents who have pre-school children in Bandung are in the state of mindful parenting or not. Furthermore, this study used Mindfulness in Parenting Questionnaire (MIPQ), compiled by McCaffrey, Reitman and Black [8]. They tested 2 dimensions, namely mindful discipline and being in the moment with child.…”
Section: Introductionmentioning
confidence: 99%
“…parenting and child care, relationships, mental health and coping, positive thinking and mindful parenting. The resource cards also include explanations about the available resources and emphasize mindfulness in parenting (Duncan et al., ; Kabat‐Zinn & Kabat‐Zinn, ; McCaffrey et al., ). The family is instructed to choose resource cards and place them in a suitable train car according to their perceptions.…”
Section: Methodsmentioning
confidence: 99%
“…For each item, the parents respond using a four‐point Likert scale. The scale has been validated among American parents with children of an average age of 6.1 years (McCaffrey et al., ). An official translation into Finnish was conducted using the ISPOR protocol (Wild et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation